Improving the aerodynamic performance of small power wind turbine blades using a computer program - غزال مريم; صلاح داوود (Latakia University Journal -Engineering Sciences Series, 2024)
A study was presented to improve the aerodynamic performance of small, horizontal-axis wind turbine blades operating at low wind speeds (V=4m/s). A study was conducted based on the design and analysis methods for the aerodynamic aspect of a small, horizontal-axis wind turbine, using the program Qblade, whose software is based on The theory of momentum of the wing element BEM. Through the analysis, the aerodynamic section (SG6043) and its aerodynamic factors (lift coefficient, drag coefficient, optimal and critical angle of attack, and Reynolds number) were chosen so that the geometric shape of the turbine blades was obtained by optimizing both the twist angle and the chord value at various stations. Qatari. As for the aerodynamic analysis method, we conducted the analytical study to obtain the most important results obtained under the influence of the factors represented in the number of blades, peripheral speed, turbine radius and root radius on each of the power, torque, thrust force, and various parameters associated with them.